Bottleneck: The Place of County Jails in California’s COVID-19 Correctional Crisis - Aviram, Hadar (2021)
This Article examines a lesser-known site of the COVID-19 pandemic: county jails. Revisiting assumptions that preceded and followed criminal justice reform in California, particularly Brown v. Plata and the Realignment, the Article situates jails within two competing/complementary perspectives: a mechanistic, jurisdictional perspective, which focuses on county administration and budgeting, and a geographic perspective, which views jails in the context of their neighboring communities. The prevalence of the former perspective over the latter among both correctional administrators and criminal justice reformers has generated unique challenges in fighting the spread of COVID-19 in jails: paucity of, and reliability problems with, data; weak and decentralized healthcare policy featuring a wide variation of approaches; and serious litigation and legislation challenges. The Article concludes with the temptation and pitfalls of relying on the uniqueness of jails to advocate for vaccination and other forms of relief, and instead suggests propagating a geography-based advocacy, which can benefit the correctional landscape as a whole